Trace - Smyčka, Václav (Dějiny – teorie – kritika, 2014)
This study describes and tries to explain the role which fragments from ‘ancient times’ played in the perception of historical time at the end of the Age of Enlightenment. In late 18th century, such valuable fragments could take the form of pieces of medieval texts found in the binding of books kept in Strahov Monastery, ruins of castles, imprints of prehistoric fl ora but even things such as collected folk poetry from the region of Kravařov. Focus shifts to the very notion of positive evidence which helps to form the framework within which such fragments presented themselves to their discoverers. It is about trying to answer the question what is a historical source, what form of factuality its ‘readers’ deal with, and how finders of such fragments situate themselves in history through such ‘traces’. This investigation thus leads both in the direction of phenomenology, to mediatedness of the specific kind of source a fragmentary ‘trace’ represents, and to a better understanding of the historical dimension of people in late 18th century.